Descriptive Analysis of Physics Learning for Biology Students at Mataram University - Sayida Magfirah; Baiq Adilya Putri Humaira Fatarani; Fina Nahdia Fitri; Alifni Aulia; Kormil Saputra; Fatima Naimi (Classroom Experiences, 2025)
Physics is one of the basic courses taught in the Biology study programme at Mataram University. Despite its important relevance in understanding biological phenomena, physics learning is often considered less interesting and relevant by biology students. This study aims to identify criticisms of physics education faced by biology students and propose solutions to improve the effectiveness of physics learning in the context of biology. This research uses descriptive quantitative method with data collection technique through questionnaires distributed to 70 first semester students from Biology study programme. Measurement indicators include learning effectiveness and level of satisfaction with physics courses. The results showed that the majority of respondents (76%) considered understanding physics as important or very important in the study of biology, especially because many biological phenomena are explained using physical principles. However, 42% of respondents stated that the physics material taught was only moderately relevant, with the main challenges being teaching methods that were not integrated with biological applications and limited mastery of basic mathematics by students. Based on these findings, the use of cooperative learning approaches and the integration of physics material with real examples of applications in biology are suggested to improve students' learning motivation and understanding. This research provides wa.